Improving the Tagg’s slope method for large-scale grounding systems through finite element method simulations - Martínez-Lozano, Miguel (Metrology and Measurement Systems, 2026)
Measurement of the grounding resistance of very large installations is difficult because conventional fall-ofpotential methods require impractically long test leads. The Tagg slope method reduces this distance, but its traditional formulation neglects finite electrode dimensions and relies on curve extrapolations outside the range originally analysed, leading to large errors.This paper revises the method using finite element simulations that model realistic electrode geometry and soil conduction. A new relationship between the slope of the voltage profile and the position of the measuring electrode is obtained and fitted by a polynomial with errors below 0.02%. The corrected method is tested on large square grounding grids and on a photovoltaic-plant grounding system. Results show that, when measurements are taken away from corner regions and with auxiliary-electrode distances above about 20% of the system diagonal, the grounding resistance can be estimated with errors below 3%, while the traditional implementation may produce errors of up to 60.